2018
DOI: 10.3390/catal8070272
|View full text |Cite
|
Sign up to set email alerts
|

The Roles of Graphene and Ag in the Hybrid Ag@Ag2O-Graphene for Sulfamethoxazole Degradation

Abstract: Ag@Ag 2 O-graphene (Ag@Ag 2 O-G) with different concentrations of graphene was synthesized using a facile in situ precipitation method. The photocatalysts were characterized by field emission scanning electron microscopy (SEM), transmission electron microscopy (TEM), X-ray diffraction (XRD), and X-ray photoelectron spectroscopy (XPS), UV-vis diffuse reflectance spectra (DRS). The antibioticsulfamethoxazole (SMX) degradationunder simulated solar light and visible light irradiationwas investigated to evaluate ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 33 publications
0
13
0
Order By: Relevance
“…As discussed in previous works [27,33,34,42], EPR studies indicated the generation of photo-induced holes and electrons, and the formation of • OH radicals when Ce-doped ZrO 2 was irradiated. Hence, to elucidate HA degradation mechanism with doped zirconia, a series of experiments were performed with disodium ethylenediaminetetraacetate (Na 2 -EDTA) (pointed as scavenger for holes [76] and a chelating agent that prevents HA adsorption on the oxide surface [73,77]) and isopropanol (commonly used as scavenger of • OH radical [77,78]). The results are shown in Figure 11.…”
Section: Resultsmentioning
confidence: 99%
“…As discussed in previous works [27,33,34,42], EPR studies indicated the generation of photo-induced holes and electrons, and the formation of • OH radicals when Ce-doped ZrO 2 was irradiated. Hence, to elucidate HA degradation mechanism with doped zirconia, a series of experiments were performed with disodium ethylenediaminetetraacetate (Na 2 -EDTA) (pointed as scavenger for holes [76] and a chelating agent that prevents HA adsorption on the oxide surface [73,77]) and isopropanol (commonly used as scavenger of • OH radical [77,78]). The results are shown in Figure 11.…”
Section: Resultsmentioning
confidence: 99%
“…Figure 6B depicts Cu 2p XPS spectra with features at 932.0, 932.5, 933.59, and 934.88 eV, which correspond to Cu 2 O, Cu, CuO, and Cu(OH) 2 phases. 43 The oxidization of Ag is followed by a dramatic increase in metallic Cu and a significant rise in the Cu(OH) 45,46 At close interfacial contact, band bending occurs, allowing for charge carrier recombination to take place between the two oxides. 7 Figure 7 depicts a proposed mechanism scheme that represents the different phases involved in the antibacterial process on Ag−Cu film samples.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Figure 6B depicts Cu 2p XPS spectra with features at 932.0, 932.5, 933.59, and 934.88 eV, which correspond to Cu 2 O, Cu, CuO, and Cu(OH) 2 phases. 43 The oxidization of Ag is followed by a dramatic increase in metallic Cu and a significant rise in the Cu(OH) 45,46 At close interfacial contact, band bending occurs, allowing for charge carrier recombination to take place between the two oxides. 7 Cu(OH) 2 is quite significant since several reports have indicated that the formation of Cu(OH) 2 is directly related to enhanced release of ROS as well as increased amounts of Cu ions, as shown in previous studies, to exhibit the antibacterial effects by disrupting ATP production and impairing bacterial cell wall.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…As seen in Figure 10 , the electrons from ZnS CB and GaOOH CB can reduce O 2 to O 2 − • active radicals due to their CB potentials which are more negative than that of O 2 /O 2 − • ( − 0.33 eV). The holes on the GaOOH VB transform OH − ions, adsorbed on the photocatalyst surface from the TC solution, to HO• because the GaOOH VB (2.83 eV) potential is higher than 1.89 eV for OH − /HO• [ 79 ]. Accordingly, the enhanced photocatalytic performance is the result of the efficient charge carriers’ separation and transport, and spatially separated reduction and oxidation sites in ZnS/GaOOH heterojunction, which act as Z-scheme heterojunction photocatalyst (confirmed by photodeposition and the ESR experiments’ results).…”
Section: Zinc Sulfide-based Heterostructures Photocatalysts For Organ...mentioning
confidence: 99%